'Cutting' and 'breaking' events in Akan - Agyepong, Dorothy Pokua (Linguistics, 2018)
This study investigates the grammar and semantics of verbs that describe separation events in Asante Twi (Akan), a Kwa (Niger-Congo) language spoken in Ghana. It adopts a constructionist approach combined with a 'monosemic bias' perspective in the analysis. It theoretical starting point is that contextual interpretations are derived from the interaction of the prototypical meanings of verbs and their arguments. A multi-method approach was used in data gathering: (i) compilation of verbs that code separation as well as sentences in which they are used from literary texts (bibles, and novels) and dictionaries. (ii) Descriptions of separation activities elicited using video-stimuli Bohnemeyer et al. (2001), 61 video clips depicting cutting and breaking events (fieldmanuals.mpi.nl) supplemented by 82 clips created by the author involving culturally appropriate objects (Agyepong 2015). (iii) Spontaneous narratives, and procedural discourses about cultural events/practices involving separation e.g. cooking, palm-wine tapping. (iv) Introspection based on the author's native speaker intuitions. The main findings of the thesis are that there are two central verbs in the separation domain in Akan: twá 'to cut' and bú 'to break'. There are, in addition, more specialized verbs for specific types of object separation, e.g. nú 'harvest palm fruit by poking with a bladed instrument' or pòrò 'to pluck fruit'. The choice of a particular verb in context is determined by the following parameters: instrument involvement, manner of separation, physical properties of entities as well as the end-state result of the situation. Crucially, the thesis further addresses the challenge of how to account for the interpretation of the typical as well as atypical argument realization patterns associated with the separation verbs. It shows how constructional meanings contribute to the interpretation of collocations of the verbs. Other principles such as coercion, addition and suppression of components in the lexical semantics of both the verbs and its arguments as well as cultural implicatures are invoked in the compositional process of calculating the contextual interpretations.